PENJUALAN BARANG IMPOR PADA E-COMMERCE: Studi Perlindungan Hukum Bagi UMKM - Boma Wikan Rekso Prasojo (2023)
Micro, Small, and Medium Enterprises (MSMEs) have become a cornerstone of Indonesia's economy, contributing at least 60% to the National Gross Domestic Product (GDP). However, MSMEs have yet to reach their full potential. Therefore, the government has designated MSMEs as the "main weapon" for developing Indonesia's economy by maximizing their potential. One of the government's strategies to unlock the potential of MSMEs is by encourage entrepreneurs in this sector to digitize their businesses by entering the Trading Ecosystem through the Electronic System (E-commerce). Nevertheless, MSMEs engaged in this digital ecosystem are at risk due to the phenomenon of imported goods flooding the e-commerce. Hence, the aim of this research is to examine how the Indonesian government, as a regulator, manages the push for the digitalization of MSMEs, regulates the sale of imported goods on e-commerce platforms, and elucidates the legal protection for MSMEs against the surge in sales of imported products on e-commerce platforms. This study employs a normative juridical method with a case approach and an analysis through descriptive-analytical methods of legislation. The findings reveal that the government has fulfilled its role in promoting digitalization as mandated by the Cipta Kerja Law. Additionally, concerning the regulation of the sale of imported products on e commerce platforms, the government has instituted several policies and regulations. To provide legal protection against the recent influx of imported goods, the Ministry of Trade has enacted Ministerial Regulation No. 31 of 2023 concerning Business Licensing, Advertising, Guidance, and Supervision of Business Actors in Trade Through Electronic Systems. This regulation is expected to foster fair competition and enhance the competitiveness of domestic products. Throughout the research, the author contends that encouraging the digitalization of MSMEs requires intensified efforts through training programs and incentives provided by the government, along with regulations favoring MSMEs. Furthermore, the author hopes that the government can mitigate the impact of such phenomena on MSMEs.